2008
DOI: 10.3386/w14279
|View full text |Cite
|
Sign up to set email alerts
|

"Might Not Be a Tomorrow": A Multi-Methods Approach to Anticipated Early Death and Youth Crime

Abstract: A number of researchers point to the anticipation of early death, or a sense of "futurelessness," as a contributing factor to youth crime and violence. Young people who perceive a high probability of early death, it is argued, may have little reason to delay gratification for the promise of future benefits, as the future itself is discounted. Consequently, these young people tend to pursue high-risk behaviors associated with immediate rewards, including crime and violence. Although existing studies lend empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 41 publications
0
37
0
Order By: Relevance
“…To be clear, individuals often weigh costs and benefits relative to some reference point; when in desperate situations, they have little to start with and therefore potential immediate rewards (no matter how objectively small or uncertain) can prove very salient, whereas potential costs are less so (Callan et al, ; McClure et al, ; Tversky and Kahneman, ; Weyland, ). Research further has shown that individuals who feel as though they have little to lose have markedly steeper discount rates (i.e., individuals place greater emphasis on immediate rewards than on later rewards) and are more accepting of risks associated with criminal behavior (Brezina, Tikan, and Topalli, ; Hill, Ross, and Low, ; Simons and Burt, ). For offenders who find themselves in adverse circumstances then, the aforementioned uncertainties associated with taking on criminal accomplices become more acceptable, as the potential gains of this group effort could alleviate adversity.…”
Section: The Decision To Co‐offendmentioning
confidence: 99%
“…To be clear, individuals often weigh costs and benefits relative to some reference point; when in desperate situations, they have little to start with and therefore potential immediate rewards (no matter how objectively small or uncertain) can prove very salient, whereas potential costs are less so (Callan et al, ; McClure et al, ; Tversky and Kahneman, ; Weyland, ). Research further has shown that individuals who feel as though they have little to lose have markedly steeper discount rates (i.e., individuals place greater emphasis on immediate rewards than on later rewards) and are more accepting of risks associated with criminal behavior (Brezina, Tikan, and Topalli, ; Hill, Ross, and Low, ; Simons and Burt, ). For offenders who find themselves in adverse circumstances then, the aforementioned uncertainties associated with taking on criminal accomplices become more acceptable, as the potential gains of this group effort could alleviate adversity.…”
Section: The Decision To Co‐offendmentioning
confidence: 99%
“…In this case, the saliency of risk and potential consequences informs risk calculation and subsequent behavior. While future perceptions are associated with risk-taking (Borowsky, Ireland, and Resnick 2009;Brezina, Tekin, and Topalli 2009;McDade et al 2011), few have examined how peers' anticipation of the future affects risky behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Although the primary focus of the aforementioned Brezina et al (2009) study was to examine how anticipated early death influences youth crime, the authors' indepth interviews with active street offenders in Atlanta also revealed potential sources of risk perception for early violent death. Brezina et al report that young offenders' fatalism "emanated from their day-to-day exposure to violence" (p. 1113), stating that "predictably, our interviewees described their own lives and neighborhoods as plagued by the persistent threat of violence" (p. 1114).…”
Section: Literature Reviewmentioning
confidence: 99%